Antituberculous Drug Resistance in Western Canada (1993 to 1994) - Richard Long; Anne Fanning; Robert Cowie; Vernon Hoeppner; Mark Fitzgerald; The Western Canada Tuberculosis Group (Canadian Respiratory Journal)
OBJECTIVES: To estimate the magnitude of antituberculous drug resistance and identify prospectively the risk factors for its development in tuberculosis (TB) patients in western Canada over a one-year period.